Advanced Experimental Medical Diagnostic System Design and Realization - Penhaker, M.; Stankus, M.; Prauzek, M.; Adamec, O.; Peterek, T.; Cerny, M.; Kasik, V. (Elektronika ir Elektrotechnika, 2012)
The aim of this work is to design and realize the experimental diagnostic instrument for biological data measurement. In the biomedical engineering daily live work is necessary to measure and analyze wide range of variables coming primary from humans or animals. There are measured mostly electrical signals from in vivo or in vitro from the subjects. Concerning these requirements we proposed the cheap and quality balanced measuring device for six channels with 2 kHz and 12 bit ADC resolution equipped with USB bus. Concerning our requirements were realized the photoplethysmography and electrocardiography module connected into measuring device to realize practical bio-signal measurements and tests. Ill. 12, bibl. 5 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.117.1.1060